The problem of value orientations in the system of humanities (philosophical and psychological aspects) - Murzina, O. A.; Nahorna, N.; Nagorny, V.; Raznatovska, O.; Pototska, O.; Мурзіна, Олена Анатоліївна; Нагорна, Наталія Олександрівна; Нагорний, Володимир Володимирович; Разнатовська, Олена Миколаївна; Потоцька, Олена Іванівна (Washington : EnDeavours Publisher, 2021)
Abstract. There is no doubt that the presence of the persistent ideological beliefs is the necessary precondition of successful work of professionals of the humanitarian profile. The formation of such beliefs is possible only under the condition of creation of system of values in the consciousness of personality. At the same time it is impossible without consideration of philosophical and psychological aspects in its preparation.
Keywords: value; value attitude; personal values